2008
DOI: 10.1007/s11232-008-0140-6
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Tauberian theorems in some problems in mathematical physics

Abstract: We give some multidimensional Tauberian theorems for generalized functions and show examples of their application in mathematical physics. In particular, we consider the problems of stabilizing the solutions of the Cauchy problem for the heat kernel equation, multicomponent gas diffusion, and the asymptotic Cauchy problem for a free Schrödinger equation in the norms of different Banach spaces among others.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…We point out that this problem was first raised and studied by Drozhzhinov and Zavialov [9,10]. Their results are robust and they demonstrated their usefulness with several very interesting applications; for example, they discovered a general abstract class of onedimensional Besov type spaces in [9], and established in [12] useful norm estimates in various Banach spaces for solutions to the Schrödinger equation. However, their theory excludes a wide number of kernels that are of great interest in harmonic analysis.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…We point out that this problem was first raised and studied by Drozhzhinov and Zavialov [9,10]. Their results are robust and they demonstrated their usefulness with several very interesting applications; for example, they discovered a general abstract class of onedimensional Besov type spaces in [9], and established in [12] useful norm estimates in various Banach spaces for solutions to the Schrödinger equation. However, their theory excludes a wide number of kernels that are of great interest in harmonic analysis.…”
Section: Introductionmentioning
confidence: 86%
“…When Γ = R n and P (∂/∂x) = ∆, we obtain that stabilization along parabolas (i.e., d = 2) is sufficient for stabilization in time of the solution to the Cauchy problem for the heat equation. This particular case of Corollary 8.12 was studied in [9,10,12]. 8.3.…”
Section: Asymptotic Stabilization In Time For Cauchy Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multidimensional Tauberian theorems were then systematically investigated by him, Drozhzhinov, and Zav'yalov, and their approach resulted in a powerful Tauberian machinery for multidimensional Laplace transforms of Schwartz distributions. Such results have been very useful in probability theory [30] and mathematical physics [1,11,29]. Tauberian theorems for other integral transforms of generalized functions have been extensively studied by several authors as well, see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This Tauberian question was raised and studied by Drozhzhinov and Zav'yalov in one dimension in [8] and in several variables in [9], where they demonstrated that many Tauberian theorems for integral transforms become particular instances of this problem. See also [10] for several other interesting applications. In this article we revisit the problem and provide optimal results by finding the largest class of test functions for which the space of E-valued distributions (up to some correction terms) admits a characterization in terms of a class estimate.…”
Section: Introductionmentioning
confidence: 99%